Non-antipsychotic medicines and modified electroconvulsive therapy are risk factors for hospital-acquired pneumonia in schizophrenia patients - Yang, Yan; Kong, Di; Li, Qiwen; Chen, Wei; Zhao, Guocheng; Tan, Xi; Huang, Xincheng; Zhang, Zipeng; Feng, Can; Xu, Min; Wan, Ying; Yang, Mi (Frontiers in Psychiatry, 2023)
Background Hospital-acquired pneumonia (HAP) has a significant and detrimental impact on schizophrenia patients. Non-antipsychotic medicines and modified electroconvulsive therapy (MECT) are frequently used in conjunction with antipsychotics to treat schizophrenia. Whether non-antipsychotic medicines or MECT are risk factors for HAP in schizophrenia treated with antipsychotics is still unknown. Methods Patients with schizophrenia who were admitted to the Fourth People's Hospital of Chengdu between January 2015 and April 2022 were included in this retrospective cohort study. Individuals with HAP were 1:1 matched to individuals without HAP (non-HAP) using propensity score matching (PSM). The risk factors for HAP were analyzed by comparing the two groups. Results A total of 7,085 schizophrenia patients were included in this study, with a mean age of 39.77 ± 14.45 years. 193 patients developed HAP on an average of 22.26 ± 21.68 days after admission with an incidence of 2.73%. After 1:1 PSM, 192 patients from each group (HAP and non-HAP) were included. The HAP group had significantly more patients with MECT and taking benzodiazepines, antidepressants, mood stabilizers, and anti-parkinsonians both before and after PSM by Bonferroni correction (P < 0.001). Multivariate logistic regression analysis showed that, combined with antipsychotics, non-antipsychotic medicines including benzodiazepines (OR = 3.13, 95%CI = 1.95-5.03, P < 0.001), mood stabilizers (OR =3.33, 95%CI =1.79–6.20, P < 0.001) and MECT (OR =2.58, 95%CI =1.49–4.46, P = 0.001) were associated with a significantly increased incidence of HAP. Conclusion The incidence of HAP in schizophrenia patients in our cohort was 2.73%. MECT and non-antipsychotic medicines, including benzodiazepines and mood stabilizers were risk factors for HAP in schizophrenia patients treated with antipsychotics.